2010
DOI: 10.1148/radiol.10091528
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Aneurysms Treated with Coil Placement: Test Characteristics of Follow-up MR Angiography—Multicenter Study

Abstract: Documentation of good diagnostic performance of TOF MR angiography at both 1.5 and 3.0 T in the current study represents an important step toward replacing intraarterial DSA with MR angiography in the follow-up of patients with aneurysms treated with coils.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
74
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(82 citation statements)
references
References 33 publications
6
74
0
2
Order By: Relevance
“…10 Another small series showed that 3T MRA had better agreement with DSA than 1.5T MRA and that coil artifacts were smaller at 3T than at 1.5T. 12 In our large series of 126 coiled intracranial aneurysms, 3D TOF-MRA at 3T was superior to 3D TOF-MRA at 1.5T to evaluate the quality of aneurysm occlusion.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…10 Another small series showed that 3T MRA had better agreement with DSA than 1.5T MRA and that coil artifacts were smaller at 3T than at 1.5T. 12 In our large series of 126 coiled intracranial aneurysms, 3D TOF-MRA at 3T was superior to 3D TOF-MRA at 1.5T to evaluate the quality of aneurysm occlusion.…”
Section: Discussionmentioning
confidence: 68%
“…[5][6][7] Both 3D TOF-MRA and CE-MRA have also been evaluated at 3T, also showing good diagnostic performance. [7][8][9][10] Direct comparison of MRA performed at 3T and 1.5T is relatively scarce, has been conducted in small series of patients, and is associated with contradictory results. [11][12][13] To compare the value of 3D-TOF at 1.5T and 3T, a prospective consecutive monocentric study was conducted in patients having follow-up examinations including DSA for coiled intracranial aneurysms.…”
Section: Abbreviationsmentioning
confidence: 99%
“…Participants were retrieved from a prospectively collected cohort of consecutive patients who were independent for activities of daily life (modified Rankin Scale (mRS) ≤3 [7]) after aSAH and who underwent digital subtraction angiography and MRA at the University Medical Center Utrecht to assess occlusion of aneurysms treated with coil placement at 18 months after aSAH [8]. For the present study, we included those patients who had been examined between May 2005 and September 2007.…”
Section: Participantsmentioning
confidence: 99%
“…1 MRA is replacing conventional angiography in following patients after coiling in many centers. 2,3 Interobserver agreement in the diagnosis of a residual or recurrent aneurysm has been reviewed recently. 4 Mean interrater agreement of the pooled studies was substantial ( ϭ 0.65; 95% confidence interval, 0.60 -0.69).…”
mentioning
confidence: 99%
“…5 Interobserver agreement by using a catheter angiographic scale directly applied to MR angiographic results has been reported as "substantial" and "similar" to angiography, but the number of readings was limited to duplicates. 3,6 A more rigorous evaluation of the agreement in the MR angiographic diagnoses of residual or recurrent aneurysms in patients treated by endovascular coiling by a larger number of observers with various expertise is needed to establish the reliability of MRA diagnoses. 7 In clinical practice, the evolution of treated aneurysms is often followed by comparing the follow-up MRA with the final catheter angiogram of the embolization procedure.…”
mentioning
confidence: 99%